STRATEGI PEMASARAN DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN MELALUI NIAT SEBAGAI MEDIASI - FEBRIAN, ANGGA; Vina Hapsari, Cinthia Annisa (Buletin Studi Ekonomi, 2019)
Marketing Strategy in Influencing Purchasing Decisions through Intention as Mediation. Changes in an increasingly dynamic era make companies have to be able to quickly follow developments that have an impact on how to do the right marketing strategy in increasing sales. Using variable marketing mix and service quality that can affect consumer intentions in buying a car. This study aims to see the effect of intention in mediating consumer purchasing decisions. The sample used is consumers who have bought cars from 2015 to 2018 in Lampung. Using the help of SmartPls software analysis software in data processing. The results of the study explained that the marketing mix had no significant effect on purchase intention while the service quality had no significant effect on purchase intention.